2018
DOI: 10.1002/hup.2657
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute alcohol withdrawal on sleep

Abstract: Specific disturbances in sleep are experienced prior to and during acute alcohol withdrawal, suggesting that tailored interventions may be effective in the treatment of sleep deficits during these periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…We did not investigate self-reported sleep or state of mood in the period prior to detoxification; therefore, we could not evaluate whether there was a sudden change in sleep or mood pattern. A previous trial on alcohol withdrawal and sleep in institutional detoxification [24] showed that poor sleep quality and insomnia were common in these patients, also prior to admission. The authors of that article discussed whether these symptoms were caused by a high alcohol intake or previous anxiety and/or depression, or if the mood alterations could be caused by insomnia [24].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We did not investigate self-reported sleep or state of mood in the period prior to detoxification; therefore, we could not evaluate whether there was a sudden change in sleep or mood pattern. A previous trial on alcohol withdrawal and sleep in institutional detoxification [24] showed that poor sleep quality and insomnia were common in these patients, also prior to admission. The authors of that article discussed whether these symptoms were caused by a high alcohol intake or previous anxiety and/or depression, or if the mood alterations could be caused by insomnia [24].…”
Section: Discussionmentioning
confidence: 91%
“…Patients entering detoxification generally report sleep disturbances. In one study, all patients showed poor sleep efficiency (range of sleep efficiency 76-91%), as measured by actigraphy during acute withdrawal [24], a value previously measured to 94% in non-dependent participants [39]. The cut-off value for sleep efficiency has been recommended to be set to 92% [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep is a major concern in those attending detoxification 5,6 and can impede treatment and recovery. 2 Hodges et al 5 reported that sleep problems were common among clients prior to admission for detoxification, with >95% scoring above clinical cut-offs for poor sleep quality, and 75% reporting severe insomnia. The most disrupted components in this setting were sleep disturbances, daytime dysfunction, and sleep quality.…”
Section: Introductionmentioning
confidence: 99%